Computationally efficient numerical technique for primary cooling zone of thin slab continuous casting. (20th January 2011) - Nath, Niloy K.; Kamble, Smita
Thin slab continuous casting process can be controlled by the water flow rate through the copper mould to obtain the proper shell thickness for a given casting speed. To achieve this, 2D model for the liquid metal flow in the strand and water flow through the mould is developed using stream function and vorticity formulation. The main advantage is faster computation, which is very important for process optimisation, and real-time modelling for process control. The funnel type shape of the mould is efficiently taken into consideration by using body fitted coordinate system. The detailed CFD-based model can be used for analysing the process parameters and variables like heat transfer through the mould flux, casting speed and superheat. The model can be easily adapted for wide range of casting process like slab and billet casting and thin strip casting.